Community-Based Education: Fostering Participatory and Practical Interfaith Tolerance through the Temanggungan Bogor Case Study, Indonesia - Putra, Ari Pratama; Sapiudin, Sapiudin; Efendi, Rachmat; Handayani, Fitri; Septiarini, Armenia; Amiros, Krey; Burhan, Burhan (Graduate School of UIN Syarif Hidayatullah Jakarta, 2025)
This qualitative case study investigates community-based educational initiatives fostering interfaith tolerance in Temanggungan Village, Bogor, Indonesia. Confronting rising intolerance and social fragmentation, the research demonstrates how participatory, context-sensitive strategies enhance multicultural awareness from childhood. Utilizing in-depth interviews, participatory observation, and documentation analysis of socio-religious activities, findings reveal that tolerance education emerges through three key mechanisms: non-formal learning frameworks, community leadership engagement, and collaborative platforms such as interfaith service projects and cultural exchange programs. Youth participation in these initiatives significantly strengthens social cohesion and intercultural understanding. The study positions this grassroots model as a viable alternative to formal education systems that inadequately incorporate multicultural principles. Policy recommendations emphasize integrating community-based approaches into national religious moderation strategies and character education curricula to address systemic gaps in value-based education. These insights contribute to global discourse on sustainable interfaith relations through localized pedagogical practices.